Pengaruh Tata Kelola Syariah Terhadap Kinerja Bank Syariah Dan Kepatuhan Syariah - Vivi Silfiana, Ika; Khanifah, Khanifah (JAKA (Jurnal Akuntansi, Keuangan, dan Auditing), 2024)
The aim of this research is to collect empirical data regarding the influence of sharia governance on sharia bank performance and sharia compliance at Bank Syariah Indonesia in Semarang City. Sharia compliance and governance are important components of risk management in Islamic banks. By providing guidance and supervision to sharia bank operations so that they consistently adhere to sharia principles, DPS plays an important role in maintaining sharia compliance. Sharia principles, sharia compliance, and observing sharia compliance are generally mandated for sharia banks. This research uses quantitative research methodology. The population of this research is Bank Syariah Indonesia employees who meet the specified requirements. The Slovin formula was used to determine the research sample, namely 36 people. Questionnaires were used to obtain data. In contrast, this research data analysis uses direct linear regression. The results of the first t test show that the tcount value is 5.870 > ttable of 1.688, the significant value is 0.000 <0.05, and the governance regression coefficient value is positive, namely 0.051. The results of the second t test show that the tcount value is 3.104 > ttable of 1.688, the significant value is 0.004 <0.05, and the governance regression coefficient value is positive, namely 0.046. Research findings show that sharia governance has a positive and significant impact on sharia bank performance and sharia compliance at Bank Syariah Indonesia in Semarang City.